(untitled) (Boletín de la Sociedad Zoológica del Uruguay, 2022)
A survey of adult mosquitoes in the area of the Palmar dam, Uruguay, was conducted from October 1980 to March 1981, prior to filling the reservoir. The Culicidae fauna consisted of 22 species in 7 genera: Aedeomyia Theobald, Aedes Meigen, Anopheles Meigen, Culex Linnaeus, Mansonia Blanchard, Psorophora Robineau-Desvoidy and Uranotaenia Lynch-Arribálzaga; the most diverse genera being Aedes (subgenus Ochlerotatus Lynch-Arribálzaga), Anopheles, Culex and Psorophora. Most abundant species was Aedes (Ochlerotatus) crinifer (Theobald), and was collected in all the sampling points. Mansonia pseudotitillans (Theobald) and Culex (Melanoconion) vaxus Dyar are recorded for the first time in Uruguay.